The development of linguistic sciences in the al-Ma'mun caliph era / Amer Ayada Ayoub Alkubaisy - Amer Ayada, Ayoub Alkubaisy (2017)
The importance of this study is due to two reasons; first: the high rank of Al Ma'mun in knowledge, scientific stature and broad culture; where he excelled in literature, language, the days of Arabs, philosophy, and previous Sciences. The second reason: the great progress, and the qualitative development of linguistic science in his era.The study aims to reveal the active and principal role of Al Ma'mun in advancing the prosperity of that era, and to refute the claim that conflicts and political strife in his time occupied his intention, weakened the ambition to build the civilization, and prevented the achievement of scientific ambition. Which invites us to build on this rare example; to show the impact of the political will of the top leadership in process of scientific development, and cultural development of the community, and consequently to benefit from this successful civilized example.The study also showed the acumen of Al Ma'mun, his political cunning in crisis management, his high ability in dealing different interests; between the suppression of sedition, and cultural and scientific development. One the fruits of his leadership was the boom of (The House of Wisdom); making it a cultural edifice and a scientific beacon that contained rooms for translation, replication, search, reading and debate. This and was a product of the openness of the Caliph on different cultures, such as Persian, Indian, Greek and Syriac, and the translation of their treasures; showering money on scholars, translators, professionals and employees in that House. All their collective efforts have effectively contributed in the process of acculturation and cross-fertilization of knowledge; which complemented studies with innovative scientific methodologies and developed the methods of research, documentation and foundation, and had the greatest impact in the prosperity of linguistic science, and advanced human civilization.